Factors Related To Maternal Fertility Of Reproductive Age At Matiti Health Center, Doloksanggul District, Humbang Hasundutan Regency - Helprida Sihite; Romasi Manalu; Nova Sontry Node Siregar; Mayes Felda Simamora (Jurnal EduHealth, 2024)
Fertility is closely related to the productive age of women, which is 15-49 years. A woman's education level is a critical variable in understanding variations in fertility rates, influencing their status, attitude, and outlook on life. Higher education levels result in longer schooling periods, shortening the reproductive period and reducing the number of children, and vice versa. The Family Planning Program focuses on Women of Childbearing Age (WCA) within this age range to reduce birth rates through sustained contraceptive use. This study aims to determine the relationship between education level, contraceptive use, and maternal fertility in Pasaribu Village. It employs quantitative research to test associative hypotheses using the chi-square test (X2) with a 95% confidence level. A probability sampling technique was used, with a sample size of 83 respondents. Data were collected through questionnaires and documentation. The results indicate a significant relationship between education level (p = 0.034), contraceptive use (p = 0.022), and maternal fertility in Pasaribu Village. The government should enhance the socialization of programs like Family Planning (FP) to reduce the economic burden on families, enabling prosperous living and positively impacting regional development. This research is crucial for the Matiti Health Center in Doloksanggul District, Humbang Hasundutan Regency, to understand the impact of education and contraception on women's fertility and inform FP programs.